COMPARATIVE ANALYSIS OF WORKING CAPITAL ON PROFITABILITY BEFORE AND AFTER OF COVID-19 PANDEMIC IN HEALTHCARE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGES - Rentina Pandora Lubis; Dudi Rudianto (Jurnal Scientia, 2023)
This study aims to determine whether Working Capital is proxied by working capital turnover, cash turnover, and receivable turnover has an effect on proxied profitability by Return on Assets (ROA) in the health care sector. listed on the Indonesia Stock Exchange before and after the Covid-19 pandemic. the data used is data from healthcare sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. the number of samples used was 80 samples with purposive sampling method. The analytical model used is multiple regression to see the effect between research variables both before and after the Covid-19 pandemic simultaneously. Then a simple regression test will be carried out to see the effect between research variables both before and after the Covid-19 pandemic partially. The results of the study partially show that Working Capital Turnover has a significant effect on profitability (ROA) both before and after the Covid-19 Pandemic, Cash Turnover has no significant effect on profitability (ROA) both before and after the Covid-19 Pandemic, and Accounts Receivable turnovers has an effect significantly to profitability (ROA) both before and after the Covid-19 Pandemic. Then the results of the study simultaneously Working Capital Turnover, Cash Turnover, and Accounts Receivable Turnover significantly influences company profitability (ROA) both before and after the Covid-19 Pandemic.